Análise da interface adesiva entre pinos de fibra de vidro e dentina intrarradicular submetida à irrigação com diferentes agentes condicionantes - Suzuki, Thaís Yumi Umeda [UNESP] (2015)
The purpose of this study was to evaluate the interaction of conditioning agents and resin cements in the luting procedure of glass fiber posts in different thirds of intra-root dentin, through the bond strength test, mechanical properties and sealing ability of the adhesive interface. Ninety single-rooted premolares human teeth were used in this study. After endodontic filling and mechanical preparation of root canal, teeth were divided into five groups according to the conditioning agents (distilled water, 5.25% sodium hypochlorite, 25% polyacrylic acid, 2% chlorhexidine and 23 ppm silver nanoparticles dispersion). Three adhesive cementation technique were adopted: Group 1: ScotchbondTM Universal self-etching adhesive + RelyX ARC resin cement, Group 2: RelyX U200 self-adhesive resin cement, Group 3: Maxcem Elite self-adhesive resin cement. The mechanical properties (Martens hardness and elastic modulus) of the adhesive interface structures (resin cement and underlying dentin) were measured in a DUH-211 digital ultra-microhardness tester (Shimadzu), under load of 5mN in different areas of intra-root dentin (cervical, middle and apical). Push-out bond strength was measured in a universal testing machine (Emic DL 3000). Sealing ability was quantified with a fluid-filtration system (Flodec) during 5 min was immediately measured. The data of bond strength and mechanical properties were subjected to statistical tests of normality and analyzed by ANOVA for repeated measures and Fisher's test (α=0.05). The results showed that the mechanical properties of Martens hardness and elastic modulus of resin cements and the underlying dentine can be influenced by conditioning agents, as well as the depth of intraradicular dentin. The same phenomenon was observed in the push-out bond strength test. The 23ppm silver nanoparticle dispersion...